Foreign direct investment, institutional quality, economic freedom and entrepreneurship in emerging markets (2014)
This study investigates the relationship between foreign direct investment, institutional quality, economic freedom, and entrepreneurship in emerging markets. The research compares the capacity and appetite for business creation among high-income, low-income and emerging countries. The results are based on a panel study of data, from 2004 to 2009 for 87 countries, using as its source “The World Bank Entrepreneurship Snapshots” to look at the connection between business creation, institutional quality, market freedom and foreign direct investment (FDI). The findings reveal a strong positive relationship between institutional quality and business generation in all three of the above categories. The freedom to create businesses and invest has an impact on business generation in emerging countries, while the influence of international trade appears more important as a spur to the genesis of business in low-income countries. Finally, there is a direct and significant relationship between FDI and business development in emerging countries. This result is consistent with “the spillover theory of entrepreneurship” (, and ).